Cancer Exosomes as Conveyors of Stress-Induced Molecules: New Players in the Modulation of NK Cell Response - Vulpis, Elisabetta (Int J Mol Sci, 2019)
Natural killer (NK) cells are innate lymphoid cells that play a pivotal role in tumor surveillance. Exosomes are nanovesicles released into the extracellular environment via the endosomal vesicle pathway and represent an important mode of intercellular communication. The ability of anticancer chemotherapy to enhance the immunogenic potential of malignant cells mainly relies on the establishment of the immunogenic cell death (ICD) and the release of damage-associated molecular patterns (DAMPs). Moreover, the activation of the DNA damage response (DDR) and the induction of senescence represent two crucial modalities aimed at promoting the clearance of drug-treated tumor cells by NK cells. Emerging evidence has shown that stress stimuli provoke an increased release of exosome secretion. Remarkably, tumor-derived exosomes (Tex) produced in response to stress carry distinct type of DAMPs that activate innate immune cell populations. Moreover, stress-induced ligands for the activating receptor NKG2D are transported by this class of nanovesicles. Here, we will discuss how Tex interact with NK cells and provide insight into their potential role in response to chemotherapy-induced stress stimuli. The capability of some “danger signals” carried by exosomes that indirectly affect the NK cell activity in the tumor microenvironment will be also addressed.